Secondary vegetation dynamics associated with cattle ranching land-use systems in Pará State - Raquel Carvalho de Lima (2018)
The increasing human intervention on the land surface has impacted climate stability and biogeochemical cycles, putting land-use and land-cover change (LUCC) in evidence as a key field of investigations in global environmental change. Considering that LUCC is to a great extent the outcome of human decisions (e.g. of actors and institutions), research in this field has used different methods and tools of investigation to go beyond the identification of drivers of LUCC, but also to focus on how human decisions operate as underlying causes of the changes observed in the physical space over time. In the Brazilian Amazon, during the last three decades, the rapid expansion of large-scale mining and agricultural activities, and especially cattle ranching, implied conversion of at least 19.55% of total primary forests, making deforestation the main process investigated in the LUCC field. However, cattle ranching is not only a main driver of deforestation but is also behind the historical accumulation of secondary vegetation which, as a result of the conversion of forests into pastures often implemented with no technical concerns, are rapidly degraded and abandoned, allowing plant regeneration and forest regrowth. In the Brazilian Amazon, until mid-2000s estimates for secondary vegetation indicated a progressive increase of this cover, however following 2010, only 1,197 km2 of additional secondary vegetation was generated, while 42,040 km2 were converted into other land-covers. Meanwhile, deforestation rates progressively decreased, being currently around 6,000 km2 in contrast to the 27,772 km2 peak in 2004, largely as a consequence of various legal and alternative coercive measures being implemented since 2004. Considering that, in this thesis I investigated the heterogeneity of processes underlying secondary vegetation dynamics in cattle ranching systems in Pará, with a particular focus on the potential impacts of changes in the strategies of actors to cope with pasture degradation. I began by investigating on a regional scale the spatial-temporal patterns of secondary vegetation cover, and how they related to spatial-temporal patterns of different land-covers in Pará. Following that, based on a field-work investigation, I aimed to understand how increased law enforcement to halt deforestation could have stimulated actors to change practices and techniques to cope with pasture degradation. Besides describing motivations, beliefs and strategies of actors, I classify the systems they operate by quantifying the practices and techniques used in pasture management and discussed how practices and techniques might have impacted secondary vegetation cover based on accumulated knowledge of its dynamics. Finally, I spatialized cattle ranching systems and performed a spatial-temporal analysis of the representativeness of clusters of secondary vegetation and pastures in each system, followed by an exploratory analysis of the associations between different categories of drivers and clusters of high and low values of secondary vegetation in different cattle ranching systems in both pre-law enforcement (i.e. 2000-2004) and post-law enforcement (i.e. 2010- 2014) periods. I have found that clusters of high values (hotspots) of secondary vegetation per deforested land prevailed in the north, while clusters of low values (cold spots) prevailed in the South of Pará, a pattern explained by the distinct regional stories of occupation and deforestation dynamics, but also by differences in the prevalence of specific land-covers. As evidenced by transitions and clusters analysis, small-scale agriculture and pastures under regeneration contributed to the concentration of high values of secondary vegetation in the north, with clean pastures being relevant to the concentration of low values in the south. Cattle ranching was in this way an important driver of change, both through conversion of secondary vegetation into clean pastures in the south and of dirty pasture and pasture under regeneration to secondary vegetation in the north. With respect to the xii adoption of practices and techniques to deal with pasture degradation, changes were restricted to regions where farming background of actors and nearness with market favored the emergence of the Professional system. In other regions, although practices and techniques with high impact in precluding pasture degradation were adopted, management is still done with low impact techniques which, in addition to other characteristics, describe the Traditional, Medium Scale and Subsistence systems. The analyses of spatial-temporal responses of secondary vegetation in each system, showed important associations between cattle ranching and secondary vegetation, especially concerning the representativeness of secondary vegetation and clean pastures. Notwithstanding, with respect to law enforcement, although observed associations between agriculture adequacy, price of bare land, and expansion of herds with clusters of high and low values of secondary vegetation can be connected with law enforcement, regardless the scale, cattle ranching operations follow decision making processes much more complex, which go beyond legal norms.